2021
DOI: 10.3389/fclim.2021.615032
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Citizen Science Data Quality

Abstract: Information about data quality helps potential data users to determine whether and how data can be used and enables the analysis and interpretation of such data. Providing data quality information improves opportunities for data reuse by increasing the trustworthiness of the data. Recognizing the need for improving the quality of citizen science data, we describe quality assessment and quality control (QA/QC) issues for these data and offer perspectives on aspects of improving or ensuring citizen science data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…This paper has also focused attention on ways in which persistent concerns about citizen science data have been addressed in the VRD program. The first of these concerns is scientific trust in citizen science data (Downs et al 2021). The solution adopted in VRD is to employ a form of itemresponse modelling to statistically quantify the ability of each participant, taking into account the difficulty of the images that they classified, and grouping them by ability levels.…”
Section: Discussionmentioning
confidence: 99%
“…This paper has also focused attention on ways in which persistent concerns about citizen science data have been addressed in the VRD program. The first of these concerns is scientific trust in citizen science data (Downs et al 2021). The solution adopted in VRD is to employ a form of itemresponse modelling to statistically quantify the ability of each participant, taking into account the difficulty of the images that they classified, and grouping them by ability levels.…”
Section: Discussionmentioning
confidence: 99%
“…However, before CS can be considered a legitimate scientific research method that produces reliable data supporting scientific and decision-making processes in various fields, including those related to monitoring water-related SDG targets, several challenges must be addressed (Burgess et al, 2017). As a positive sign for formulating a CS approach to monitoring SDGs, numerous studies have shown that volunteers can collect data of a comparable quality to professional scientists (Downs et al, 2021;Sullivan et al, 2014) Creating a proper workflow is crucial in all the CS-based projects which influence motivation and performance (Sprinks et al, 2017). This CS project for SDG 6 monitoring is framed with four stages, as shown in Figure 2.…”
Section: Framework Design and Discussionmentioning
confidence: 99%
“…To ensure transparency and assist repository users in making informed decisions about data reuse, documentation of data quality and quality assurance measures performed at the level of individual datasets is necessary (Downs et al 2021;Peng et al 2022). Currently, the availability of data quality information is limited, whereas, ideally, it should be published in a machine-readable format, taking both researchers' and service providers' perspectives into account (Assante et al 2016).…”
Section: Data Quality Informationmentioning
confidence: 99%